Satisfaction and perceived quality in major outpatient surgery - Javier Cruz Rodríguez; Carrel Niomylesh Niome Abreus; Leosbel Armenteros Fleites; María Margarita Ríos Cabrera; Yasmani Martínez López; María del Carmen Rodríguez Fernández (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2023)
Background: quality is one of the issues that has aroused the greatest interest in researchers from the most dissimilar branches of production, services and science in recent years. The need to study the perceived quality in the health field and, particularly, in major outpatient surgery has been demonstrated. Objective: to evaluate the satisfaction and quality perceived by patients and relatives who use major outpatient surgery; to determine the existence of differences in the patients and relatives' criteria. Methods: descriptive observational study from January 2018 to March 2020 at the General Surgery Service of the Arnaldo Milián Castro Provincial Hospital, in Santa Clara. Telephone interviews were applied to 50 patients (operated for major outpatient surgery) and a family member who had accompanied them during the care process. Results: favorable results were obtained in satisfaction and quality perception in patients and relatives without showing significant statistical differences between these groups. Conclusions: major ambulatory surgery is a care modality well accepted by patients and their accompanying families.